Perlindungan Hukum Bagi Konsumen Dalam Transaksi Handphone Rekondisi - Guntur Guntur; Nirwan Junus; Julius T. Mandjo (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
The purpose of this study is to determine the legal protection of consumer rights and buying and selling transactions for reconditioned mobile phones according to Article 4 of Law Number 8 of 1999 concerning Consumer Protection. The research method used is empirical, namely a science based on real events or events that have been experienced by the five human senses obtained from observations, experiences and experiments that have been carried out. The results of this study are legal protection for consumers against trade in electronic reconditioned goods in Gorontalo City, one of which is regulated in Law Number 8 of 1999 concerning Consumer Protection in Article 8 paragraph (2) regulates and protects consumers from fraudulent actions that may be carried out by business actors, where protection is provided in the form of goods that are priced according to the information provided. The practice of buying and selling reconditioned mobile phones carried out by mobile phone traders in Gorontalo is not in accordance with Law Number 8 of 1999 concerning Consumer Protection Article 4 letter c which explains the rights that consumers have when buying and selling because in reality the seller does not provide information in full on the goods traded to prospective buyers.